Testing and modeling HpGe detector with anti-Compton shield - Tursunbayev, N; Urazbekov, B. A. (Eurasian Journal of Physics and Functional Materials, 2026)
Simulating with GEANT4 of anti-Compton shield containing eight BGO scintillators that works on anti-coincidence with HpGe detector was presented. The coefficient value of Compton tail suppression on 60Co spectrum was taken by simulating and from experiment. Comparing results of experimental data with simulating were presented. The influence of anti-coincidence inclusion on the detector efficiency was determined with simulation.Recommended CitationTursunbayev, N. T. and Urazbekov, B. A. (2020) "Testing and modeling HpGe detector with anti-Compton shield," Eurasian Journal of Physics and Functional Materials: Vol. 4: No. 3, Article 3.DOI: https://doi.org/10.29317/ejpfm.2020040303